(untitled) - Hambley, Allan R.; Allan R. Hambley (Upper Saddle River, New Jersey)
A clear introduction to electrical engineering fundamentals.Electrical Engineering: Principles and Applications. 6e helps students learn electrical- engineering fundamentals with minimal frustration. Its goals are to present basic concepts in a general setting. to show students how the principles of electrical engineering apply to specific problems in their own fields. and to enhance the overall learning process. Circuit analysis. digital systems. . electronics. and electromechanics are covered A wide variety of pedagogical features stimulate student interest and engender awareness of the materials relevance to their chosen profession
Keywords: Electrical engineering